Histochemical Studies on the Tongue of Goat Foetii (Capra hircus) - Dar, Yousuf; Sarma, Kamal; Suri, Shalini; Devi, Jonali (Indian Journal of Veterinary Anatomy, 2015)
The present study was conducted on the tongue of 18 goat foetii divided into three prenatal age groups to study the distribution of histochemical moieties. The content of neutral mucopolysaccharides, basic proteins and glycogen in the lamina epithelialis, propria-submucosa, sketetal muscles and various glands of the tongue increased with advancing prenatal age. The reaction of acidic mucopolysaccharides in different structures of tongue was weak to moderate at all ages, except the lingual and Von Ebner’s glands which showed strong positive reactions for the same towards advanced gestational age.